Sara Mañero, "El Arcipreste de Talavera" de Alfonso Martínez de Toledo - Aurelio González Pérez (Medievalia, 2016)
Sara Mañero, "El Arcipreste de Talavera" de Alfonso Martínez de Toledo, Toledo: Instituto Provincial de Investigaciones y Estudios Toledanos, 1997 (Monografías, 48). 494 pp.